Modeling 3D Canopy Structure and Transmitted PAR Using Terrestrial LiDAR. Issue 2 (4th March 2017) - Cifuentes, Renato; Van der Zande, Dimitry; Salas, Christian; Tits, Laurent; Farifteh, Jamshid; Coppin, Pol
Abstract: The heterogeneity and 3-dimensional (3D) organization of forest canopy elements is highly linked with the spatial variability of within and below canopy light. Using terrestrial LiDAR we studied the influence of several parameters in efficiently building 3D canopy models, and quantified below canopy light in 2 forest stands using ray-tracing. A voxel-based approach was used for canopy modeling, and a series of forest scenes were built for calculation of simulated structural variables (e.g., leaf area index, canopy openness). Through hypothesis testing, we found that simulated variables were consistent with the observed ones depending on: forest type, voxel size utilized in 3D modeling, and the zenith angle ranges used for calculations. Following below canopy light simulations were performed considering these 3 aspects. On average, estimates of light being transmitted overestimated measured light, and variance in below canopy light was maximum at lower values of measured light. This study presented a method to objectively define 3D modeling parameters for an efficient characterization of canopy structure, allowing to simulate trends in radiation flux transmitted to the forest floor. Improvements in the modeling process and ray-tracing parameterization were suggested.